Remote Sensing Image Fusion - Alparone, Luciano; Aiazzi, Bruno; Baronti, Stefano; Garzelli, Andrea (Signal and Image Processing of Earth Observations, 2015)
A synthesis of more than ten years of experience, this book covers methods specifically designed for remote sensing imagery. The authors supply a comprehensive classification system and rigorous mathematical description of advanced and state-of-the-art methods for pansharpening of multispectral images, fusion of hyperspectral and panchromatic images, and fusion of data from heterogeneous sensors such as optical and synthetic aperture radar (SAR) images and integration of thermal and visible/near-infrared images. They also explore new trends of signal/image processing, such as compressive sensing and sparse signal representations.